(untitled) (Herald of Journalism, 2020)
In article the comparative and comparative method investigates the purpose, tasks, structure, function and specific features of oratorical skill and other art forms. There are conducted the important provisions in the theoretical plan since the time of the wisdom Lukpan, Akikar, wise Socrates and Anakharsis and also – since an era of Abay and up to now, continu- ous scientific researches about eloquence art. The humanistic principles which are the cornerstone of oratory are confirmed by various examples. In research we rely on opinions of outstanding persons, such as al-Farabi and Abay to show the importance of oratory, its informative function, condi- tions under which works are created an oratorical skill.